Body fat assessment by computed tomography and radiography in normal Beagle dogs - KIM, Doyeon (J Vet Med Sci, 2018)
The purpose of this study was to determine the relationships among body condition score (BCS), radiography, and computed tomography (CT), and to establish a method for body fat assessment on CT in dogs. Thirty eight Beagles with 2 to 7 BCS were examined. Subcutaneous fat thickness (ST) on radiograph and body area (BA), total fat area (TA), subcutaneous fat area (SA), and visceral fat area (VA) on CT were measured at the level of L3 and L6 vertebra. Ratios of each value to the L6 length were obtained ((r)ST, (r)TA, (r)SA, (r)VA) and the correlations with BCS were estimated. The value of VA/SA, VA/TA, TA/BA, VA/BA, and SA/BA were selected for measuring fat and the correlations with BCS were estimated. The (r)ST, (r)TA, (r)SA, and (r)VA were significantly correlated with BCS, and the (r)TA and (r)SA were significantly correlated with (r)ST. At the level of L3, (r)TA and (r)VA had stronger relationships with BCS than at L6 while (r)SA had a higher correlation with BCS at L6. The TA/BA, VA/BA, and SA/BA were significantly correlated with BCS, and the upper limits were 15.11, 6.31, and 8.92%, respectively. Our results showed that CT could be useful to assess body fat and TA/BA, VA/BA, and SA/BA are suitable criteria for measuring fat on CT. In addition, L3 was a more suitable location for evaluating total and visceral fat, and L6 was more suitable for evaluating subcutaneous fat.